Production of zinc oxide from hazardous waste - Sal Ammoniac Skimming - Piroskova J. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2018)
This article deals with hydrometallurgical treatment with the subsequent precipitation of zinc from hazardous waste Sal- Ammoniac Skimming produced in wet hot-dip galvanizing process. Chemical analysis showed that skimming contained 46.64% Zn. X-ray diffraction analysis identified the Zn(OH)Cl phase (96.36%) and NH4Cl (3.64%) in Sal-Ammoniac Skimming. The skimming was first subjected to leaching in order to extract zinc into the solution containing HCl, followed by precipitation of the zinc. The experiments were performed in a medium of HCl at concentrations of 0.25, 0.5, 1 and 2M. Complete dissolution of zinc was achieved in 0.5M HCl solution, at 40°C, L:S=20, max. 30 min. The apparent activation energy of leaching reaction by hydrochloric acid solution was Ea=5.543 kJ mol-1. Zn precipitation was carried out using Na2CO3 and NaOH. Zinc oxide with a purity of about 99% was obtained directly from the solution of 6M NaOH at a temperature of 60°C – 80°Cat pH 8.8.